The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1046/j.1525-1497.2000.08014.x
|View full text |Cite
|
Sign up to set email alerts
|

A physician survey of the effect of drug sample availability on physicians’ behavior

Abstract: OBJECTIVE: Pharmaceutical companies often use drug samples as a marketing strategy in the ambulatory care setting. Little is known about how the availability of drug samples affects physicians' prescribing practices. Our goal was to assess: (1) under what circumstances and why physicians dispense drug samples, (2) if drug samples lead physicians to use medications other than their preferred drug choice, and (3) the physician characteristics that are associated with drug sample use. DESIGN:Cross-sectional surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
153
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(160 citation statements)
references
References 15 publications
(16 reference statements)
4
153
0
3
Order By: Relevance
“…Many reasons are given for physicians distributing drug samples rather than writing prescriptions that would necessitate a visit to the pharmacy. [9][10][11][12] According to physicians and other individuals polled (e.g., medical residents, nurses, pharmacists, participants in medical continuing education, pharmaceutical sale representatives), samples save the patient from having to go to the drugstore; reduce the cost of treatment; allow the patient to gain access to new treatments while allowing the physician to develop clinical experience and use new drugs that may not yet be covered by public or private plans; allow rapid initiation of therapy, which may be needed for clinical reasons; and allow the physician to verify short-term tolerance or efficacy before writing a prescription for the usual duration of therapy. The use of samples may even increase the patient's level of satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reasons are given for physicians distributing drug samples rather than writing prescriptions that would necessitate a visit to the pharmacy. [9][10][11][12] According to physicians and other individuals polled (e.g., medical residents, nurses, pharmacists, participants in medical continuing education, pharmaceutical sale representatives), samples save the patient from having to go to the drugstore; reduce the cost of treatment; allow the patient to gain access to new treatments while allowing the physician to develop clinical experience and use new drugs that may not yet be covered by public or private plans; allow rapid initiation of therapy, which may be needed for clinical reasons; and allow the physician to verify short-term tolerance or efficacy before writing a prescription for the usual duration of therapy. The use of samples may even increase the patient's level of satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][13][14][15] For example, the distribution of drug samples may jeopardize the continuity of care, especially as the patient's medication record at the retail pharmacy will be incomplete and the pharmacist is unlikely to meet the patient during the course of therapy with drug samples. These omissions can lead to unintended therapeutic duplication, allergic reactions, intolerances or interactions, doses that are too low or too high, use of contraindicated drugs, and missed opportunities to counsel patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some argue that samples lead to overuse of expensive, brandname, medications in lieu of less expensive, evidence-based, treatments. 4 Despite these limitations, we found that 78% of elderly Medicare beneficiaries with CRN accessed free samples. We argue that the needs of these patients should be considered when adopting policies limiting free sample distribution.…”
mentioning
confidence: 85%
“…The most useful research in this direction is probably the sparse literature in medicine that examines the motives of physicians while dispensing free samples to the patients. Such motives could emanate from factors such as: (1) financial savings; (2) convenience; (3) immediate initiation of therapy (4) demonstrating appropriate use of drugs; (5) adjustment of doses; (6) evaluating effectiveness of adverse effects of drugs (Chew, et al, 2000;Duffy and Clark, 2003) Studies (Gönül et al, 2001) have revealed that detailing has a positive and significant effect on doctors prescription of specific brand of drugs. Others find that detailing has a very modest effect (Mizik and Jacobson, 2004) or no effect at all (Rosenthal et al, 2003) on brand prescriptions or sales ( Leeflang et al, 2004) pointed that the incongruent effects of detailing are mainly due to the marketing expenditure made by the firms across different brands.…”
Section: Effects Of Pharmaceutical Crm On the Prescription Generationmentioning
confidence: 99%